1988
DOI: 10.1002/em.2850110108
|View full text |Cite
|
Sign up to set email alerts
|

A method for studying the mutagenicity of some gaseous compounds in salmonella typhimurium

Abstract: A dynamic flow-through exposure system was designed for mutagenicity studies of gaseous compounds in Salmonella. Salmonella typhimurium strain TA100 was the primary tester strain. The dose ranges were 0.5-20% of vinyl chloride, ethene, propene, and 1,3-butadiene, 1-200 ppm of ethylene oxide, 0.5-20 ppm of nitrogen dioxide, and 0.1-3.5 ppm of ozone. The gas flow rate was 250, 500, or 1,000 ml/min, and the exposure time was 6 or 7 hours. Of the tested gases, vinyl chloride, ethylene oxide, and nitrogen dioxide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…EtO is a tobacco smoke toxicant and was selected for use in this study as it is a direct acting genotoxic agent with known mutagenic properties in vitro and in vivo [Victorin and Stahlberg, ; Agurell et al, ; Thier and Bolt, ]. A 2‐year exposure to EtO was found to preferentially induce GGT → GTT mutations at codon 12 of K‐ ras in the lung tumours of B6C3F1 mice [Hong et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EtO is a tobacco smoke toxicant and was selected for use in this study as it is a direct acting genotoxic agent with known mutagenic properties in vitro and in vivo [Victorin and Stahlberg, ; Agurell et al, ; Thier and Bolt, ]. A 2‐year exposure to EtO was found to preferentially induce GGT → GTT mutations at codon 12 of K‐ ras in the lung tumours of B6C3F1 mice [Hong et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…EtO has previously been shown to be highly mutagenic in Salmonella typhimurium strain TA100 when tested at concentrations of 1–200 ppm in a continuous flow system over a 6 hr exposure period, both in the presence and absence of a rat S9 metabolic activation system [Victorin and Stahlberg, ]. Further evidence of a mutagenic effect of EtO in the Ames assay was detailed in a study where Salmonella typhimurium strains TA100 and TA1535 were exposed to EtO for 4 hr in suspension culture, plated on minimal agar and cultured for 48 hr before scoring of the resulting colonies.…”
Section: Discussionmentioning
confidence: 99%
“…NO 2 is very reactive and thought to be toxic to microorganism. It has been reported that NO 2 caused chromosome aberrations in cultured Chinese hamster (Tsuda et al, 1981) and mutations in Salmonella typhimurium (Victorin and Stahlberg, 1988). One group (Kosaka et al, 1986) bubbled a NO 2 gas into 5 mL fractions for 30 min at a flowrate of 0.1 L/min and found wild type E. coli was resistant to 90 ppm NO 2 .…”
Section: The Effect Of Gas Impuritiesmentioning
confidence: 99%
“…In spite of the formation of its carcinogenic metabolite EO, ET was found to be negative in mutagenicity studies in vitro and in vivo in rodents (Victorin and Ståhlberg, 1988; Walker et al , 2000) and in a long-term carcinogenicity study in rats (Hamm et al , 1984). The negative outcome of the carcinogenicity study was expected from toxicokinetic studies with ET and EO in rats and from studies on hemoglobin adducts in rats and mice.…”
mentioning
confidence: 99%